Dissecting the Re-Os molybdenite geochronometer. Issue 1 (December 2017) - Barra, Fernando; Deditius, Artur; Reich, Martin; Kilburn, Matt; Guagliardo, Paul; Roberts, Malcolm
Abstract Rhenium and osmium isotopes have been used for decades to date the formation of molybdenite (MoS2 ), a common mineral in ore deposits and the world's main source of molybdenum and rhenium. Understanding the distribution of parent187 Re and radiogenic daughter187 Os isotopes in molybdenite is critical in interpreting isotopic measurements because it can compromise the accurate determination and interpretation of mineralization ages. In order to resolve the controls on the distribution of these elements, chemical and isotope mapping of MoS2 grains from representative porphyry copper-molybdenum deposits were performed using electron microprobe and nano-scale secondary ion mass spectrometry. Our results show a heterogeneous distribution of185, 187 Re and192 Os isotopes in MoS2, and that both187 Re and187 Os isotopes are not decoupled as previously thought. We conclude that Re and Os are structurally bound or present as nanoparticles in or next to molybdenite grains, recording a complex formation history and hindering the use of microbeam techniques for Re-Os molybdenite dating. Our study opens new avenues to explore the effects of isotope nuggeting in geochronometers.